Clinical features and outcomes of infective endocarditis in Egypt: an 11-year experience at a tertiary care facility - Hussein Hassan Rizk; Ahmed Adel Elamragy; Ghada Sayed Youssef; Marwa Sayed Meshaal; Ahmad Samir; Ahmed ElSharkawy; Karim Said; Hussien Heshmat Kassem; Mervat Gaber Elanany; Amani Ali El-Kholy; Al Sayed Akl; Soheir M. Mahfouz; et al. (The Egyptian Heart Journal, 2019)
Abstract Background Few data are available on the characteristics of infective endocarditis (IE) cases in Egypt. The aim of this work is to describe the characteristics and outcomes of IE patients and evaluate the temporal changes in IE diagnostic and therapeutic aspects over 11 years. Results The IE registry included 398 patients referred to the Endocarditis Unit of a tertiary care facility with the diagnosis of possible or definite IE. Patients were recruited over two periods; period 1 (n = 237, 59.5%) from February 2005 to December 2011 and period 2 (n = 161, 40.5%) from January 2012 to September 2016. An electronic database was constructed to include information on patients’ clinical and microbiological characteristics as well as complications and mortality. The median age was 30 years and rheumatic valvular heart disease was the commonest underlying cardiac disease (34.7%). Healthcare-associated IE affected 185 patients (46.5%) and 275 patients (69.1%) had negative blood cultures. The most common complications were heart failure (n = 148, 37.2%), peripheral embolization (n = 133, 33.4%), and severe sepsis (n = 100, 25.1%). In-hospital mortality occurred in 108 patients (27.1%). Period 2 was characterized by a higher prevalence of injection drug use-associated IE (15.5% vs. 7.2%, p = 0.008), a higher staphylococcal IE (50.0% vs. 35.7%, p = 0.038), lower complications (31.1% vs. 45.1%, p = 0.005), and a lower in-hospital mortality (19.9% vs. 32.1%, p = 0.007). Conclusion This Egyptian registry showed high rates of culture-negative IE, complications, and in-hospital mortality in a largely young population of patients. Improvements were noted in the rates of complications and mortality in the second half of the reporting period.